The development of fast and slow inferential responding: Evidence for a parallel development of rule-based and belief-based intuitions. - Markovits, Henry; de Chantal, Pier-Luc; Brisson, Janie; Gagnon-St-Pierre, Émilie (Memory & Cognition, 2019)
Dual process theories postulate the existence of two levels of processing, Type 1, which uses belief-based cues to make very rapid inferences, and Type 2, which uses more conscious, working memory-based processes that are, in principle, capable of making rule-based judgments. There is a common assumption that Type 1 processes are more rapidly produced, while Type 2 processes take more time. Evidence for this assumption is mixed. Recently, Newman, Gibb, and Thompson (Journal of Experimental Psychology: Learning, Memory, and Cognition, 43(7): 1154, 2017) have provided clear evidence that very fast responses use a combination of both belief-based and rule-based cues. In these studies, we initially replicated this basic result with adults using a different methodology and extended them to examine in greater detail patterns of change with restricted time. The results also show the same combination of rule-based and belief-based cues in fast responses, and suggest that time constraints differentially affect each form of cue. We then examined the developmental pattern of both fast and slow responding. Children aged between 8 and 10 years of age were examined using the methodology of the initial study. Results show that both developmental patterns and the effect of reduced time on children produce parallel changes in both belief-based and rule-based responding. These results suggest the existence of two simultaneously developing processes, consistent with a dual-strategy model of reasoning.